Urban Farming Development Strategy of Hydroponic Vegetables in Bekasi City - Esi Asyani Listyowati; Ahya Kamilah; Haris Budiono; Ridwan Lutfiadi (UNIVED Press, Dehasen University Bengkulu, 2023)
Urban Farming is one of the important Bekasi City Government’s programs to strengthen the food security, considering the increase in agricultural land conversion. This research aims to determine the internal and external factors influencing the development of community’s hydroponic vegetable business (HVB), alternative strategies for developing the community’s HVB, and priority order of competitive strategies to be implemented in the development of the community’s HVB in Bekasi City. Descriptive method was used in this research, supported by data analysis using IFE, EFE, SWOT, IE, and QSPM matrices. The total IFE matrix score was 2.4, indicated the hydroponic community's average ability in responding to the internal environment. The total EFE matrix score was 1.98, showed its low ability to respond to the external. The IE matrix implied the hydroponic community’s position in cell VIII or in the harvest and divest position. Based on the SWOT matrix, four alternative strategies have been obtained in priority order, which also have been analyzed by using the QSPM matrix; (1) revitalization of the urban farming-development program, (2) market facilitation of hydroponic community production, (3) promotion of hydroponic vegetables as fresh vegetables, and (4) education for hydroponic community.